1994
DOI: 10.1002/jbmr.5650090715
|View full text |Cite
|
Sign up to set email alerts
|

Do variations in hip geometry explain differences in hip fracture risk between japanese and white americans?

Abstract: Despite lower femoral neck bone mass, Japanese women have a substantially lower incidence of hip fracture than North American whites. Reasons for this discrepancy were sought in a study of 57 Japanese and 119 white American women aged 50-79. All women were in good health. Bone mineral content (BMC) in the femoral neck, femoral neck length (NL), femoral neck angle (theta), cross-sectional moment of inertia (CSMI), safety factor (SF), and fall index (FI) were calculated using dual x-ray absorptiometry. Height an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
2
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(58 citation statements)
references
References 11 publications
4
49
2
3
Order By: Relevance
“…Loss of trabecular bone of the supero-lateral one half of the femoral neck (A-P projection) parallels the higher rates of bone loss seen in the supero-lateral one half of the cortex (represented here by the S, S-A, and S-P sectors) when contrasted to the infero-medial one half. (25,26) Hip fracture cases had no excess of trabecular bone loss beyond that expected to occur through normal aging, confirming our previous results. (27) In consequence, candidates for hip fracture depend on their trabecular bone for more than one half of their s cr , because they suffer a preferential loss of cortical bone that becomes severe with advanced age.…”
Section: Discussionsupporting
confidence: 89%
“…Loss of trabecular bone of the supero-lateral one half of the femoral neck (A-P projection) parallels the higher rates of bone loss seen in the supero-lateral one half of the cortex (represented here by the S, S-A, and S-P sectors) when contrasted to the infero-medial one half. (25,26) Hip fracture cases had no excess of trabecular bone loss beyond that expected to occur through normal aging, confirming our previous results. (27) In consequence, candidates for hip fracture depend on their trabecular bone for more than one half of their s cr , because they suffer a preferential loss of cortical bone that becomes severe with advanced age.…”
Section: Discussionsupporting
confidence: 89%
“…They found a higher proportion of fractures in women of Asian descent, a factor not controlled for in our study. Nakamura et al found that women of Japanese descent had lower neckshaft angles than white American women, and Japanesedescent women could be an at-risk subset of the population 17 . This stresses the importance of obtaining imaging of both femora in patients with a history of atypical femoral fracture and thigh pain.…”
Section: Discussionmentioning
confidence: 99%
“…Among the geometrical parameters, HAL [12][13][14] and NSA [15][16][17] have been under investigation for years in relation to hip fracture, using radiographs and DXA data. It is difficult to maintain a good positioning of the hip joint so as to be able to analyze the geometry using such techniques as HAL and NSA in the radiographs and DXA after hip fracture, since the legs are usually abducted and outwardly rotated 18) .…”
Section: Discussionmentioning
confidence: 99%